2016
DOI: 10.3233/jad-160569
|View full text |Cite
|
Sign up to set email alerts
|

Theobromine-Induced Changes in A1 Purinergic Receptor Gene Expression and Distribution in a Rat Brain Alzheimer’s Disease Model

Abstract: Dementia caused by Alzheimer's disease (AD) is mainly characterized by accumulation in the brain of extra- and intraneuronal amyloid-β (Aβ) and tau proteins, respectively, which selectively affect specific regions, particularly the neocortex and the hippocampus. Sporadic AD is mainly caused by an increase in apolipoprotein E, a component of chylomicrons, which are cholesterol transporters in the brain. Recent studies have shown that high lipid levels, especially cholesterol, are linked to AD. Adenosine is an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 47 publications
0
33
1
Order By: Relevance
“…Dietary cholesterol has been widely recognized as one of the best approaches to modeling sporadic AD in rabbits [1, 4, 35], rats [5759], mice [48, 60], and guinea pigs [61]. Previous studies show that high cholesterol diet can increase TNF-α expression in mice [48, 49] and rats [62], our data revealed dietary cholesterol concentrations increased TNF-α expression in the rabbit hippocampus, suggesting dietary cholesterol can model a persistent TNF-α elevation in hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary cholesterol has been widely recognized as one of the best approaches to modeling sporadic AD in rabbits [1, 4, 35], rats [5759], mice [48, 60], and guinea pigs [61]. Previous studies show that high cholesterol diet can increase TNF-α expression in mice [48, 49] and rats [62], our data revealed dietary cholesterol concentrations increased TNF-α expression in the rabbit hippocampus, suggesting dietary cholesterol can model a persistent TNF-α elevation in hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its effect on the increase in soluble Aβ has been detected, suggesting a protective role for A 1 agonists [41]. On the other hand, it has been reported that a fat-enriched diet induced cognitive and memory dysfunctions as well as a reduction in the A 1 hippocampal receptors that were reverted by the A 1 receptor's antagonist, theobromine [42].…”
Section: Adenosine and Admentioning
confidence: 98%
“…Moreover, theobromine showed prophylactic neuroprotection against damage to cognitive functions and levels of Aβ when 30 mg/L were added to drinking water. The authors suggest that the reducing Aβ effect could be mediated by the antioxidant and anti-inflammatory capacities of theobromine via decreased SOD1 and NFκB levels [49]. Moreover, theobromine isonucleotide analogs were synthesized and evaluated as active compounds in the inhibition of cholinesterases, since their low cytotoxicity makes them interesting as therapeutic molecules for AD [50].…”
Section: Animal Studies/molecular Pathwaysmentioning
confidence: 99%